Influence Of Implant-Abutment Connection Design On Peri-Implant Bone Loss: A Prospective Study (The Review of Diabetic Studies, 2025)
Background: The maintenance of peri-implant marginal bone is important for the long-term success and aesthetics of dental implants. Of the many factors that influence the stability of crestal bone, the design of the implant-abutment connection is of significant interest. Data suggest that internally conical connections, in conjunction with platform-switching, may inhibit bacterial microleakage, decrease micromovement at the connection interface and waste less stress on mechanical loads than external or internal hexagonal connections. However, clinical data are heterogeneous and there are few high-quality prospective trials directly comparing these designs.Objective: The goal of this forward-looking clinical study was to assess the effect of three different designs of implant-abutment connection: External Hexagon (EH), Internal Hexagon (IH) and Internal Conical (IC) with and without platform-switching on peri-implant marginal bone level over a follow-up of 36 months.Materials and Methods: A total of 180 implants were placed in partially edentulous adults and randomly assigned to three different groups of connections (60 each). Standard surgical and prosthetic protocols were performed on all individuals. Marginal bone levels were measured on calibrated periapical radiographs at implantation (baseline), and then after 6, 12, 24 and 36 months. Secondary clinical parameters measured included probing pocket depth, bleeding on probing, implant survival and complications to the prosthesis. Statistical analyses were performed using mixed models in order to account for repeated measures and clustering of patients.Expected Outcomes: Implants with internal conical and platform-switched designs are expected to show significantly less marginal bone loss than external hexagon connections. The study will provide clinically relevant evidence to assist clinicians in making informed decisions about implants and designing the prosthesis to achieve improved peri-implant tissue stability.